Shell waste valorization to chemicals: methods and progress - Korampattu, Lavanya; Ghosh, Neha; Dhepe, Paresh L. (Green Chemistry, 2024)
In light of growing energy and resource demands, the conversion of biomass materials into diverse chemicals and fuels holds significant importance. This process enables the utilization of biomass as a valuable and renewable resource to meet these escalating needs. The current biomass valorization processes are largely based on plant-derived lignocellulosic biomass materials. Studying new genres of biomass materials and their value addition is highly desirable, and they would complement and expand the existing biorefinery system. Crustacean shell waste represents a highly potential bioresource that is composed of a set of useful chemicals, among which chitin, the amino polysaccharide, has come to the fore as a promising material for a plethora of applications. In terms of the abundance of biopolymers on Earth, cellulose is the most prevalent biopolymer, and chitin ranks as the second. The presence of biologically fixed nitrogen in the structure of chitin opens up new possibilities for making useful chemicals, notably nitrogen-containing chemicals, which are otherwise impossible to produce directly from lignocellulosic biomass. In the last two decades, several attempts have been made by researchers in this area to convert chitin and its derivatives into valuable chemicals. This review comprehensively summarizes the transformation of the chitin fraction from shell waste to various chemicals through different thermo-catalytic processes and appraises the advancements in this area. The effect of various catalytic systems on chitin biomass valorization processes and the challenges and opportunities allied to this are discussed. This review summarises the thermo-catalytic processes converting chitin from shell waste into diverse chemicals and reviews the advances, catalytic systems, and associated challenges.